Compound heterozygous variants in Wiskott-Aldrich syndrome like (WASL) gene segregating in a family with early onset Parkinson's disease. (March 2021) - Kumar, Sumeet; Abbas, Masoom M.; Govindappa, Shyla T.; Muthane, Uday B.; Behari, Madhuri; Pandey, Sanjay; Juyal, Ramesh C.; Thelma, B.K.
Abstract: Background: Knowledge of genetic determinants in Parkinson's disease is still limited. Familial forms of the disease continue to provide a rich resource to capture the genetic spectrum in disease pathogenesis, and this approach is exploited in this study. Methods: Informative members from a three-generation family of Indian ethnicity manifesting a likely autosomal recessive mode of inheritance of Parkinson's disease were used for whole exome sequencing. Variant data analysis and in vitro functional characterisation of variant(s) segregating with the phenotype were carried out in HEK-293 and SH-SY5Y cells using gene constructs of interest. Results: Two compound heterozygous variants, a rare missense (c.1139C > T:p.P380L) and a novel splice variant (c.1456 + 2 delTAGA, intron10) in Wiskott-Aldrich syndrome like gene ( WASL, 7q31), both predicted to be deleterious were shared among the proband and two affected siblings. WASL, a gene not previously linked to a human Mendelian disorder is known to regulate actin polymerisation via Arp2/3 complex. Based on exon trapping assay using pSPL3 vector in HEK-293 cells, the splice variant showed skipping of exon10. Characterisation of the missense variant in SH-SY5Y cells demonstrated: i) significant alterations in neurite length and number; ii) decreased reactive oxygen species tolerance in mutation carrying cells on Tetrabutylphosphonium hydroxide induction and iii) increase in alpha-synuclein protein. Screening for WASL variants in two independent PD cohorts identified four individuals with heterozygous but none with biallelic variants. Conclusion: WASL, with demonstrated functional relevance in neurons may be yet another strong candidate gene for autosomal recessive PD encouraging assessment of its contribution across populations. Highlights: Whole exome sequencing in a three-generation PD family of Indian ancestry. Identification of putative disease causal compound heterozygous variants in WASL . In vitro assay of splice variant in HEK-293 cells shows exon skipping. In vitro analysis of missense variant in SH-SY5Y cells shows altered protein function and increase in α-synuclein levels.